Planning and Risk Analysis in Projects of Procurement of Agricultural Raw Materials for the Production of Environmentally Friendly Fuel - Tryhuba, Anatoliy; Komarnitskyi, Serhii; Tryhuba, Inna; Hutsol, Taras; Yermakov, Serhii; Muzychenko, Andrii; Muzychenko, Tetiana; Horetska, Iryna (International Journal of Renewable Energy Development, 2022)
The purpose of the research is to substantiate the method of planning the need for technical equipment of corn waste collection projects for the production of environmentally friendly fuel, which is based on simulation of work taking into account the changing design environment.  During the research, the methods of simulation modeling of corn waste collection projects for the production of environmentally friendly fuel were used. The methods of probability theory and mathematical statistics were used, which provided the substantiation of models of natural-climatic and production conditions of corn waste collection projects for the production of environmentally friendly fuel.  As a result of the conducted research the method and statistical simulation model of planning  the need for  technical equipment of projects on collecting the waste of corn for production of environmentally friendly fuel has been  developed. They provided an assessment of the timely implementation of work in selected fields, taking into account the changing design environment, which leads to the risk of the specific cost of corn waste disposal.  A simulated model for the collection of maize waste available for disposal, provided that the balance of organic carbon in the fields is maintained, and tested for adequacy according to the Mann-Whitney test. Based on the use of the developed simulation model, the indicators of the use of technical equipment and the trend of changing the risk of the specific cost of disposal of corn waste are substantiated. Rational scenarios for the implementation of projects for which there are no risks for a given project environment are identified.